Dobutamine-stress magnetic resonance microimaging in mice : acute changes of cardiac geometry and function in normal and failing murine hearts. - Wiesmann, F; Ruff, J; Engelhardt, S; Hein, L; Dienesch, C; Leupold, A; Illinger, R; Frydrychowicz, A; Hiller, K; Rommel, E; Haase, A; Lohse, M; et al. (2001)
The aim of this study was to assess the capability of MRI to characterize systolic and diastolic function in normal and chronically failing mouse hearts in vivo at rest and during inotropic stimulation. Applying an ECG-gated FLASH-cine sequence, MRI at 7 T was performed at rest and after administration of 1.5 microgram/g IP dobutamine. There was a significant increase of heart rate, cardiac output, and ejection fraction and significant decrease of end-diastolic and end-systolic left ventricular (LV) volumes (P<0.01 each) in normal mice during inotropic stimulation. In mice with heart failure due to chronic myocardial infarction (MI), MRI at rest revealed gross LV dilatation. There was a significant decrease of LV ejection fraction in infarcted mice (29%) versus sham mice (58%). Mice with MI showed a significantly reduced maximum LV ejection rate (P<0.001) and LV filling rate (P<0.01) and no increase of LV dynamics during dobutamine action, indicating loss of contractile and relaxation reserve. In 4-month-old transgenic mice with cardiospecific overexpression of the beta(1)-adrenergic receptor, which at this early stage do not show abnormalities of resting cardiac function, LV filling rate failed to increase after dobutamine stress (transgenic, 0.19+/-0.03 microL/ms; wild type, 0.36+/-0.01 microL/ms; P<0.01). Thus, MRI unmasked diastolic dysfunction during dobutamine stress. Dobutamine-stress MRI allows noninvasive assessment of systolic and diastolic components of heart failure. This study shows that MRI can demonstrate loss of inotropic and lusitropic response in mice with MI and can unmask diastolic dysfunction as an early sign of cardiac dysfunction in a transgenic mouse model of heart failure.